NT

rút gọn biểu thức sau : A = ( x-2 ) ^2 + ( x+3 ) ^2 - 2 . ( x + 1) ( x-1)

 

KA
28 tháng 5 2017 lúc 19:46

A = (x - 2)2 + (x + 3)2 - 2.(x + 1)(x - 1)

A = (x - 2)2 + (x + 3)2 - 2.(x2 - 1)

A = x2 - 2.2x + 22 + x2 + 2.3x + 32 - 2x2 + 2

A = 2x + 15

Bình luận (0)
TC
28 tháng 5 2017 lúc 19:48

\(A=\left(x-2\right)^2+\left(x+3\right)^2-2\left(x+1\right)\left(x-1\right)\)

\(A=x^2-4x+4+x^2+6x+9-2\left(x^2-1\right)\)

\(A=2x^2+2x+13-2x^2+2\)

\(A=2x+15\)

Bình luận (0)
TT
28 tháng 5 2017 lúc 19:50

Ta có:  A = ( x-2 ) ^2 + ( x+3 ) ^2 - 2 . ( x + 1) ( x-1)

<=> A = ( x- 4x + 4) + ( x- 6x + 9) - 2. (x- 1)

<=> A=  ( x- 4x + 4) + ( x- 6x + 9) - (2x- 2)

<=> A=  x- 4x + 4 + x- 6x + 9 - 2x2  + 2

<=> A=  - 10x + 15

<=> A=  15 - 10x !!!

Bình luận (0)
TG
28 tháng 5 2017 lúc 19:51

kết quả là:

   2x + 15

       đs...

Bình luận (0)
KK
28 tháng 5 2017 lúc 19:58

A= 2x + 15

Bình luận (0)
NT
28 tháng 5 2017 lúc 20:16

cảm ơn các bạn

Bình luận (0)